2014
DOI: 10.1103/physrevb.90.035423
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance of disordered graphene: From low to high temperatures

Abstract: We present the magnetoresistance (MR) of highly doped monolayer graphene layers grown by chemical vapor deposition on 6H-SiC. The magnetotransport studies are performed on a large temperature range, from T = 1.7 K up to room temperature. The MR exhibits a maximum in the temperature range 120 − 240 K. The maximum is observed at intermediate magnetic fields (B = 2 − 6 T), in between the weak localization and the Shubnikov-de Haas regimes. It results from the competition of two mechanisms. First, the low field ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Equation further predicts the absence of an EEI correction when μB=1, that is a fixed point where R(B=1/μ) does not depend on T . This is indeed observed in very good approximation in the complete data, and has also been found in slightly different graphene samples . The presented picture has been possible due to the independent analysis of WL and EEI.…”
Section: Large‐area Monolayer Graphenesupporting
confidence: 81%
“…Equation further predicts the absence of an EEI correction when μB=1, that is a fixed point where R(B=1/μ) does not depend on T . This is indeed observed in very good approximation in the complete data, and has also been found in slightly different graphene samples . The presented picture has been possible due to the independent analysis of WL and EEI.…”
Section: Large‐area Monolayer Graphenesupporting
confidence: 81%
“…To further illustrate this interesting behavior, we expand the plot of r xx (B) at high T in Fig. 5(b) and nd that there is a crossover from negative to positive MR with increasing T. Jabakhanji et al 33 observed positive magnetoresistance (MR) in highly doped graphene grown by chemical vapor deposition on SiC and argued that it is due to the energy dependence of mobility that is prominent at high T. This dependence may result from scattering by ionized impurities or by phonons produced at the graphene/SiC interface. In their work at low T the T-independent crossing point in r xx (superimposed on the background parabolic negative MR) was observed when the product of mobility and magnetic eld is equal to 1 and is presumably due to electron-electron interaction corrections.…”
Section: Resultsmentioning
confidence: 96%
“…The antilocalization occurs in spite of the very weak spin-orbit coupling in graphene, but is suppressed in the presence of short-ranged impurities; these restore weak localization by allowing backscattering between the inequivalent K and ′ K valleys. Elsewhere, other works have explored the nature of the interaction-related correction to graphene's conductance [27][28][29][30][31][32] , and have found it to be of similar magnitude to that arising from weak localization.…”
mentioning
confidence: 99%
“…In both the original experimental work on quantum corrections in normal metals and semiconductors [1][2][3]5 , and in more recent investigations performed on graphene [13][14][15][16][17][18][19][20][21][22][23][24][27][28][29][30][31][32] , the primary emphasis has been on obtaining information on these phenomena by studying their influence on the equilibrium charge transport conductance. More specifically, most works have addressed the manner in which the corrections are affected by a magnetic field, which breaks time-reversal symmetry and suppresses weak localization while leaving the interaction contribution unaffected [1][2][3][4][5] .…”
mentioning
confidence: 99%